China the middle kingdom ([S.l.] : Highlight International Films [production company] ; Kuala Lumpur : Visual Resources [distributor])
This program explores the history, economic conditions, culture and social life, people in China
Produced by Highlight International Films in association with Link House Communications
Keywords: China -- History; China -- Social life and customs; China -- Economic conditions